DO TEACHERS USE VIDEOS FROM YOUTUBE IN A TEACHING AT THE SECOND LEVEL OF BASIC SCHOOL? - BUDINOVA, Vendula (Trends in education, 2018)
In the 20th century, media such as radio or television have emerged for communicating information. It has now been supplemented by media that are related to information technologies, such as computers, the Internet and touch devices. These media have been gradually integrated into the education process, where they play an important role today. In 2005, a new platform emerged on the internet to share video files. It was a YouTube social network (www.youtube.com). In the amount of videos that are growing on this platform each day, there are also those that contain, in addition to the entertainment component, information and education (e.g. travel vlogs, vlogs about politics, vlogues about historical events, etc.). Videos containing the informational and educational component can serve as external motivation of pupils in teaching. We have responded to these facts in our research survey, where we focused on the YouTube social network when this network is used by teachers in the school environment as a motivational element for pupils at elementary school.
Keywords: Socialnetworks; YouTube; videos; motivation.